Development of an innovative differentiated learning model for inclusive education in the independent elementary school curriculum - Asnita Hasibuan; Berman Hutahaean; Charles Andre F. Nieves (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study addresses the limited availability of empirically validated differentiated learning models for inclusive elementary classrooms within the Merdeka Curriculum. It aims to develop and examine the feasibility, practicality, and effectiveness of an innovative differentiated learning model for Indonesian language instruction in an inclusive elementary school. The study employed research and development using the ADDIE model and involved two Indonesian language teachers, 67 fifth-grade students, and three expert validators at SD Santo Petrus Medan Johor. The resulting products consist of a teacher handbook and a student workbook integrating diagnostic assessment, learner-profile mapping, differentiated content-process-product pathways, and adaptive assessment. Expert validation placed the model in the highly feasible category (86.75%). Practicality was also high, as indicated by teacher responses (88.40%) and student responses (85.60%). Effectiveness testing revealed an increase in learning outcomes from 70.85 to 82.30 with a moderate N-gain of 0.39, while students’ social skills improved by 15.20%. These findings indicate that the developed model is feasible, practical, and effective for strengthening inclusive, adaptive, and student-centered learning. The study contributes an operational syntax-based model that bridges inclusive education principles and the Merdeka Curriculum in elementary Indonesian language learning.